Grenada : Climate Change Policy Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
Grenada has made significant strides to counter climate change but meeting the daunting remaining challenges will require domestic policy actions and sustained international support. Climate change is an existential threat to Grenada. Increasing frequency and intensity of coastal storms threatens infrastructure and livelihoods, as do increased risk of coastal flooding and drought. Notably, Hurricane Ivan in 2004 caused damages of over 200 percent of GDP. Grenada has recognized this by placing climate resilience at the center of its policy making and forging strategic alliances with key global climate finance providers. However, the challenges facing the country remain daunting and will require large increases in international support, both financial and technical, to assist the Grenadian authorities turn their impressive resilience plans into action.